Amalan Pengurusan Risiko Bagi Meningkatkan Prestasi Projek Pembinaan Perumahan - Shafien, Nur Khalilah (Research in Management of Technology and Business, 2023)
The construction industry is a risky industry but it plays an important role in driving the economic growth of developed and developing countries. Construction project management is important to ensure the best performance can be achieved through the completion of the project on time, meeting the cost, quality and set standards. However, there are various risks inherent in construction projects that become constraints such as time and cost exceeding the value of the construction, building materials and work quality that do not meet specifications and also inappropriate design factors. Therefore, the objective of this study is to identify the causes of risk for the performance of housing construction projects, identify the steps practiced by developers in managing the effects of risk and identify suggestions for improvement for risk management in improving the performance of housing construction projects. This study uses a quantitative method through the distribution of questionnaires to respondents. The respondents of this study consisted of 40 respondents from housing developers in Selangor where the response rate was 33%. The data analysis method used in this study is statistical descriptive and uses the Staticical Package for Social Science (SPSS) software. The results of the study have identified the main cause of risk on the performance of the housing construction project is a location that is not suitable in terms of geography, economy and social. In addition, the steps practiced by developers in managing the impact of risk on the performance of housing construction projects are related to knowing how a risk occurs, analyzing risk to determine methods in risk mitigation and risk assessment to implement control strategies for unacceptable risks. Among the suggested improvements for risk management in improving the performance of housing construction projects is to make construction project risk management more efficient. Therefore, this study is important in focusing on the construction industry and can help developers to adopt better risk management methods to ensure that the performance of housing construction projects can be improved and can achieve success in terms of cost, time and quality.